Fostering Inclusivity: Fitting Learning Methods With The Needs of Deaf Students at SLB Ma’arif NU Lamongan - Wahyudi, Winarto Eka; Masuwd, Mowafg Abrahem (Didaktika Religia, 2024)
Every child possesses an equal entitlement to receive high-quality education, including those with auditory impairments. Delivering Islamic education to deaf students poses distinctive challenges, necessitating a tailored instructional approach. SLB Ma’arif NU Lamongan exemplifies a commitment to diversity through the implementation of a differential learning strategy to cater to the educational requirements of deaf students. This study endeavors to scrutinize the application of the aforementioned learning approach within the Islamic education framework for deaf students at SLB Ma'arif NU Lamongan, with a particular focus on comprehending the methodologies and tactics employed to address varied learning needs. Employing a qualitative research methodology, the study incorporates observations, in-depth interviews with educators and administrative personnel, and analysis of curriculum documents. Thematic analysis is utilized to discern recurring patterns and themes pertaining to the execution of the learning approach. The findings reveal the adoption of a differential learning model to accommodate the diverse requirements of deaf students in Islamic education. This approach entails the customization of lesson plans tailored to individual students’ levels of hearing impairment, leveraging sign language and assistive technologies, and deploying both individualized and collaborative learning strategies. Furthermore, the institution cultivates an inclusive educational milieu conducive to the spiritual, cognitive, and emotional development of deaf learners. This research contributes to elucidating the significance of adapting instructional methodologies to address diverse learning needs and cultivating an inclusive learning environment to ensure equitable educational opportunities for all students, irrespective of their auditory capabilities.